Results of external quality control study in flow cytometric acute lymphoblastic leukemia diagnostics - A. M. Popov; T. U. Verzhbitskaya; E. E. Zueva; O. V. Anan’eva; E. V. Babenko; L. V. Baydun; E. A. Belyakova; E. V. Boyakova; O. G. Bortnikova; M. V. Gorchakova; L. Yu. Grivtsova; E. N. Grinkevich; et al. (Онкогематология)
Comparison of interpretation of acute lymphoblastic leukemia (ALL) flow cytometric diagnostics data was the aim of the study. Immunophenotyping data obtained from 10 patients with ALL were analysed separately in 26 laboratories from Russian Federation and Kazahstan. Results comparison showed four main type of discordance: B-lineage ALL diagnostics during heavy bone marrow regeneration, great variability of T-ALL interpretation, complexity of ambiguous lineage acute leukemia and, finally, very different report types, unique for each laboratory. All these problems are the serious obstacles for standardization of flow cytometric ALL diagnostics in multicenter setting. Continuation of similar QC rounds following by consecutive discussions with further development of consensus diagnostic algorithm could be the first step for standardization of ALL immunophenotyping in Russian Federation and CIS countries.